Zero-carbon sulfur-free magnesium repairing material based on crystal water flow promotion and sintering performance regulation and control method thereof
By developing zero-carbon sulfur-free magnesium repair materials based on crystallization water flow promotion, and using the method of rapid reaction and release of crystallization water, the pollution, long sintering time and sulfur-increasing pollution of traditional magnesium carbonaceous repair materials are solved, and rapid sintering and efficient steelmaking of repair materials are achieved.
Patent Information
- Application Number
- CN202510076454.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-17
AI Technical Summary
Traditional magnesium carbonaceous hot repair materials have problems such as pollution of the environment, long sintering time and sulfur-increasing pollution, which is difficult to meet the steel industry's demand for green and environmentally friendly and efficient steelmaking.
Develop a zero-carbon sulfur-free magnesium repair product based on crystallization water flow promotion. Through the combination of magnesium chloride hexahydr, strontium chloride hexahydr and magnesite, it uses crystallization water to quickly react and release, forming a sol product to bind aggregate and matrix, and accelerate the sintering process.
It realizes rapid sintering of repair materials, shortens the sintering time, improves the medium and high temperature strength and slag corrosion resistance of the repair material layer, and meets the needs of green and environmentally friendly and efficient steelmaking.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure BDA0005247235470000021
Abstract
Description
Technical Field
[0001] The invention relates to a zero-carbon and sulfur-free magnesium repair material based on crystal water flow promotion and a method for regulating and controlling sintering performance thereof, and belongs to the technical field of refractory materials for hot repair of steelmaking converters. Background Art
[0002] For a long time, magnesium-carbon hot repair materials with asphalt as a binder, also known as "black material" and "large material", have been widely used in local hot repairs of various converters during their service life because of their good fluidity, strong resistance to slag penetration, high bonding strength between the repair layer and the original brick layer, and stable structure under thermal shock. However, as the steel industry places increasingly high demands on green environmental protection, efficient steelmaking, and clean steel quality, the shortcomings of magnesium carbon repair materials have been gradually exposed and magnified: (1) When heated, its asphalt binder easily volatilizes toxic substances such as anthracene, phenol, formaldehyde, (3,4) benzopyrene, etc., which seriously pollutes the working environment and cannot meet environmental protection requirements; (2) Asphalt is usually a by-product of coal or petroleum produced by coking, distillation and other processes, and inevitably contains a high level of sulfur. The use of magnesium carbon repair materials will have a serious sulfur-increasing pollution effect on molten steel, especially for high-quality clean steel with strict sulfur control. Traditional magnesium carbon repair materials are strictly prohibited; (3) The sintering time is too long. Since asphalt softens at low temperatures, it needs to be hardened at a higher temperature (complete hardening requires up to 500°C or above). It often takes more than 40 minutes from the beginning of softening to complete hardening, resulting in the sintering time required for magnesium carbon repair materials being too long and unable to meet today's high-efficiency steelmaking needs.
[0003] In order to solve the above problems of traditional magnesium carbon repair materials, some relevant scholars have learned from the self-flowing characteristics of castables, used various magnesium sands as the main raw materials, used micro / nano-grade SiO2 as a binder, and added high-efficiency water reducers to develop a series of environmentally friendly water-based magnesium repair materials for converters, also known as water-based large-scale materials, water-mixed materials, etc. Before hot repair, the water-based magnesium repair material is prepared into a slurry with a self-flowing effect by adding a certain amount of water, and then it is put into the converter using a scrap steel trough. With the operation of shaking the furnace, the repair slurry will gather to the potholes to be repaired under the action of tilting, and the purpose of repair will be achieved after sintering and solidification. Obviously, water-based magnesium repair materials have indeed solved the problems of traditional magnesium-carbon repair materials, such as environmental pollution, long sintering time, and molten steel resulfurization. This is also the reason why it is expected to replace the traditional magnesium-carbon repair materials as the most popular product in recent years, and has attracted the attention of more and more refractory scientific and technological workers, and a large number of known and public intellectual property technical solutions have emerged, such as CN115385668A, CN116751067A, CN106747505A, etc. Although water-based magnesium repair materials have solved the problems of traditional magnesium-carbon materials, they have also brought many new problems: (1) The production cost is high, and its benefit improvement cannot match the cost increase, and it is not competitive under current conditions; (2) Water needs to be added in advance to prepare mud on site, which increases the work intensity in front of the furnace. At the same time, the amount of water added fluctuates greatly due to human factors, and the repair quality is difficult to control; (3) Due to the excessive addition of free water in the early stage of repair, the original furnace lining is greatly damaged. It is precisely because of these objective problems that the large-scale promotion and application of water-based magnesium repair materials are hindered. Summary of the invention
[0004] In response to the problems existing in the above-mentioned water-based magnesia repair materials, the present application proposes a zero-carbon and sulfur-free magnesia repair material based on crystal water flow promotion and a method for regulating its sintering performance. After being heated, the repair material reacts rapidly to release a large amount of crystal water, and quickly forms a sol product with the SiO2 micropowder particles and the lightly burned MgO particles produced by the in-situ decomposition of hydromagnesite in the system. This sol product can not only effectively bond the aggregate and matrix in the repair material, exert a preliminary bonding effect and enhance the medium and low temperature strength of the repair material layer, but also accelerate the flow-promoting effect of the slurry on the aggregate. After the water evaporates and the sintering reaction is completed, a solid sintered layer of repair material can be formed in the furnace lining to be repaired area, thereby achieving the purpose of rapid furnace repair.
[0005] In order to solve the above problems, the specific technical solution of the present invention is as follows: a zero-carbon and sulfur-free magnesium repair material based on crystal water flow promotion, characterized in that it is made of the following raw materials in parts by weight:
[0006]
[0007] The above components add up to 100% and are mixed to form a basic repair material.
[0008] The magnesia is one or more of sintered magnesia or fused magnesia, and the MgO content of the magnesia raw material is ≥80wt%.
[0009] The purity of the strontium chloride hexahydrate is ≥99wt%.
[0010] The repair material also needs to be added with a high-efficiency water reducing agent, and the added proportion is 0.3wt% to 0.5wt% of the basic repair material.
[0011] The high-efficiency water reducing agent is one of polyethylene glycol, sodium tripolyphosphate, lignin sulfonate or polycarboxylate.
[0012] The preferred high-efficiency water reducing agent is polyethylene glycol, with a particle size of ≤200 mesh.
[0013] The repair material also needs to be added with metal aluminum powder, the addition ratio of which is 2wt% to 5wt% of the basic repair material, and the particle size of the aluminum powder is ≤200 mesh.
[0014] The specific sintering performance control method based on magnesium repair material includes the following steps:
[0015] Step 1: Understand the basic data of the converter to be repaired: focus on the residual temperature T of the furnace during the converter repair 余 , the amount of single repair material Y and the specific sintering time t given in front of the furnace 给 ;
[0016] Step 2: Use Y and t obtained in step 1 给 Calculate the sintering time coefficient ζ of a ton of material according to the following formula;
[0017] ζ= t 给 / Y (Formula 6)
[0018] Step 3: Use the ζ calculated in step 2 and T obtained in step 1 余 , refer to the table below to select the ratio of aluminum powder to hydromagnesite, i.e. the optimal value of A / H;
[0019] Table 4 Selection table of the best recommended values of A / H determined by furnace temperature and sintering time coefficient
[0020]
[0021] Step 4: According to the optimal value of A / H selected in step 3, the minimum addition ratio (Al) wt% of metal Al powder is calculated as follows:
[0022] (Al) wt% = (A / H) × (hydromagnesite) wt% (Formula 7)
[0023] Step 5: Increase the (Al) wt% value calculated in step 4 by 10% as the final addition ratio of metal aluminum powder, and introduce it in the form of external addition, so that the repair material can be heated to the residual temperature T 余 Conditions, sintering time is adjusted to t 给 The purpose within this range can well meet the production rhythm of steelmaking in front of the furnace.
[0024] The zero-carbon and sulfur-free magnesium dry repair material based on crystal water flow promotion of the present application adopts the above components and has the following advantages:
[0025] 1. Magnesium chloride hexahydrate, strontium chloride hexahydrate and hydromagnesite are used to release crystal water in situ to promote flow, replacing the traditional water-based magnesium repair material that needs to be mixed with water into mud, which can greatly reduce the secondary damage of water to the furnace lining body;
[0026] 2. Since the repair material provided in this application is put into the furnace as dry material, there is no need to add water on site to prepare mud. The total amount of in-situ crystallization water released can be accurately controlled by adjusting the amount of hydromagnesite, magnesium chloride hexahydrate, and strontium chloride hexahydrate added, thereby achieving the purpose of independently regulating the density and sintering performance of the repair material layer;
[0027] 3. At the repair working temperature, the magnesium oxide particles produced by the decomposition reaction of hydromagnesite and magnesium chloride hexahydrate have a large specific surface area and high reaction activity, which is conducive to promoting solid-phase sintering; and the CO2 and HCl gases produced by the decomposition can effectively increase the internal atmosphere pressure of the repair material layer, and enhance the power of water discharge from the body; an appropriate amount of Al powder is added, which is used to react rapidly with the released crystal water, accompanied by a violent heat release effect, from initiation to compensation for the endothermic cooling problem caused by the decomposition reaction of hydromagnesite, magnesium chloride hexahydrate, and strontium chloride hexahydrate in the repair material system, providing temperature guarantee for the sintering process. The synergistic effect of the above three aspects makes the repair material provided by this application have good sintering performance and shortens the required sintering time.
[0028] 4. The highly active MgO particles produced by the decomposition of hydromagnesite and magnesium chloride hexahydrate in the components can not only accelerate the solid-phase sintering reaction process, but also react in situ with the SiO2 micropowder particles and metal Al powder hydrothermal reaction products in the components to generate high-melting-point forsterite (melting point of about 1890°C) and magnesium-aluminum spinel (melting point of about 2135°C), reducing the amount of liquid phase generated by the material system at the working temperature, forming a highly directly bonded microstructure, and improving the medium and high temperature strength of the repair material layer; in addition, the above-mentioned in-situ reactions are accompanied by a certain volume expansion effect, which effectively blocks the pores in the repair material layer caused by the escape of crystal water, hydration products, CO2 and other components, realizes tissue densification, and effectively improves the repair material's resistance to slag erosion and penetration. Therefore, the repair material provided by this application has a high service life and good durability.
[0029] 5. The present invention cleverly utilizes the characteristics of low crystallization water release temperature and large water discharge of strontium chloride hexahydrate. It is used in combination with magnesium chloride hexahydrate to effectively reduce the crystallization water release temperature of magnesium chloride hexahydrate, increase the water discharge speed, and greatly enhance the ability of the repair material to quickly form self-flowing performance. In addition, strontium chloride has a boiling point of 1250°C. At the operating temperature of the converter, it will gradually volatilize and be discharged from the repair material layer, which has little effect on the refractoriness and durability of the repair material system.
[0030] 6. This application does not add sulfur-containing raw materials such as asphalt, and the C in the hydromagnesite in the component exists in the form of carbonate, which can be completely decomposed into CO2 and discharged during the sintering and static process of the repair material. There is no risk of carbon increase and sulfur regeneration in the molten steel. Therefore, the magnesium repair material provided in this application is a veritable zero-carbon and sulfur-free product that can fully meet the current green and clean steelmaking needs. DETAILED DESCRIPTION
[0031] A zero-carbon and sulfur-free magnesium repair material based on crystal water flow promotion, characterized in that it is made of the following raw materials in parts by weight:
[0032]
[0033] The above components add up to 100% and are mixed to form a basic repair material.
[0034] In order to further improve the high temperature fluidity of the repair material and obtain excellent sintering performance, the following additives are generally added to the above basic repair material formula:
[0035]
[0036] Furthermore, the magnesia is one or more of sintered magnesia or fused magnesia, which serves as the main raw material in the formulation system and is the main part of the repair layer. Therefore, in order to obtain good high-temperature performance of the repair material, this solution requires that the MgO content of the magnesia raw material is ≥80wt%;
[0037] Furthermore, the magnesium chloride hexahydrate is an industrial-grade chemical raw material with a white granular appearance, and its main component is MgCl2·6H2O, and the present application requires that its content is ≥98wt%. Magnesium chloride hexahydrate is the main carrier for in-situ release of crystal water in the present technical solution, and its theoretical crystal water content is as high as about 53.1%. However, without adding other components, its heating change process is usually divided into the following stages:
[0038] Stage 1, temperature 96-117°C:
[0039] MgCl2·6H2O=MgCl2·4H2O+2H2O (Formula 1)
[0040] Stage 2, temperature 135~180℃:
[0041] MgCl2·4H2O=MgCl2·2H2O+2H2O (Formula 2)
[0042] Stage 3, temperature 185-230°C:
[0043] MgCl2·2H2O=MgCl2·H2O+2H2O (Formula 3)
[0044] Stage 4, when the temperature is above 230°C:
[0045] MgCl2·H2O=Mg(OH)Cl+HCl↑ (Formula 4)
[0046] Stage 5, when the temperature is above 527°C:
[0047] Mg(OH)Cl=MgO+HCl↑ (Formula 5)
[0048] It can be seen that in the absence of interference from other components, the crystal water inside magnesium chloride hexahydrate is gradually released and discharged in three stages under heating conditions, and the temperature window width of each stage is about 20 to 50 ° C, and the release rate of each window period is about 17.7%. In addition, when magnesium chloride hexahydrate is above 527 ° C, the final product is high-temperature phase MgO. Therefore, for this application, magnesium chloride hexahydrate is a relatively ideal crystal water carrier with high water content, high water yield and good terminal product. However, the shortcomings of magnesium chloride hexahydrate are also obvious, mainly because of its high water outlet temperature and large gaps between each drainage window period, which causes discontinuous release of crystal water, and it is impossible to quickly form a large number of continuous water aggregation areas, causing the released water to be quickly evaporated without being fully wetted and combined with the silica powder in the system, thereby greatly weakening the technical effect of the present application having an in-situ production of mud with a self-flowing effect, which will greatly reduce the flow properties of zero-carbon and sulfur-free magnesium repair materials. To overcome this shortcoming, the present application will introduce two components, strontium chloride hexahydrate and hydromagnesite, as auxiliary carriers of crystal water and accelerated release agents of magnesium chloride hexahydrate crystal water, to maximize the ability of the material system to quickly form a water aggregation zone at the repair temperature.
[0049] The strontium chloride hexahydrate is a hydrated strontium salt crystal material with a white granular appearance. The theoretical crystal water content in its crystal structure is about 40.5%, and it is basically released and discharged in three temperature stages: that is, 4 molecules of crystal water are discharged when heated to about 61°C, and when the temperature reaches 100°C and 150°C, 1 molecule of crystal water is lost each. It can be seen that strontium chloride hexahydrate not only has a high crystal water content, but also has a low discharge temperature and a fast release rate, and is a more ideal crystal water carrier. However, due to the low melting point and boiling point of the terminal product (SrCl2) after heating, although SrCl2 will evaporate completely at the use temperature, a large number of evaporative pores generated by adding too much strontium chloride hexahydrate will be unfavorable to the high temperature strength, durability and other performance of the repair material. Therefore, this application can only introduce it in a small amount in the form of an additive. It should be noted that the purpose of adding strontium chloride hexahydrate in this application is mainly two: one is to release a certain amount of crystal water before magnesium chloride hexahydrate, so as to quickly merge with some SiO2 micropowder particles in the system to form a sol mucosa with a large viscosity. Under the uniform wrapping effect of the sol mucosa, the surface of the magnesium chloride hexahydrate particles will become a closed "quasi-vacuum" state. This "quasi-vacuum" effect can effectively reduce the release temperature of the crystal water of magnesium chloride hexahydrate by about 25-50°C, and reduce the drainage window gap by 3-5°C, so that the release process of the crystal water of magnesium chloride hexahydrate tends to be concentrated and continuous to the greatest extent. In addition, the crystal water release stage and window temperature of strontium chloride hexahydrate complement and connect with magnesium chloride hexahydrate, which can further promote the rapid formation of a large number of continuous water aggregation areas in the entire crystal water carrier to achieve a flow-promoting effect; second, strontium chloride has a low melting point of only 874°C, and it is very easy to form a liquid phase that promotes the migration of solid particles during the sintering process of the repair material, thereby achieving the effect of promoting sintering. In order to achieve the above purpose to the greatest extent, this application requires that the purity of strontium chloride hexahydrate is ≥99wt%, and the particle size is preferably 0mm-1mm.
[0050] In order to study the effect of the ratio of the addition amount of the two crystal water carriers, magnesium chloride hexahydrate and strontium chloride hexahydrate, on the high-temperature fluidity of the zero-carbon and sulfur-free magnesium repair material, the inventor controlled the total amount of the two to be added at 20wt% and kept it unchanged, and only adjusted the mass ratio of the two from 1:1 to 5:1 in turn. On the basis of the same other raw material components and the same particle grading scheme, they were fully mixed and prepared into different repair material samples. Weigh 300g of each sample separately, and quickly put it into the bottom of a special resistance furnace with a furnace temperature of 1200℃ with a round material spoon. After closing the furnace door and keeping warm for 10 minutes, the repair material sample is plated into a round cake shape. The high-temperature fluidity of the sample is measured by the size of the round cake area, that is, the larger the round cake area, the better the fluidity of the repair material. However, in order to improve the accuracy, it is required that the test be operated by the same person throughout the whole process, and the action of placing the material into the furnace each time is uniform and the technique is consistent to ensure that the initial state of the round cake is the same. The final test results are shown in Table 1.
[0051] Table 1 Effect of different addition ratios of magnesium chloride hexahydrate and strontium chloride hexahydrate on high temperature fluidity of repair material
[0052]
[0053] As can be seen from Table 1, the blank sample without strontium chloride hexahydrate has the worst fluidity. This is because the discharge temperature of the crystallization water of magnesium chloride hexahydrate is high and discontinuous, and a continuous water aggregation zone cannot be formed in the system. With the addition of strontium chloride hexahydrate, the discharge of the crystallization water of magnesium chloride hexahydrate can be effectively promoted. When the ratio of the amount of magnesium chloride hexahydrate to strontium chloride hexahydrate added reaches 3:1, the promotion effect is the best, and the high-temperature fluidity performance is the best. Therefore, this application fixes the ratio of the amount of the two crystallization water carriers of magnesium chloride hexahydrate and strontium chloride hexahydrate to 3:1 (mass).
[0054] Under the condition that the ratio of magnesium chloride hexahydrate to strontium chloride hexahydrate is maintained at 3:1, the inventors have conducted a lot of research on the effect of strontium chloride hexahydrate addition on the fluidity and post-firing apparent porosity of zero-carbon and sulfur-free magnesium repair materials. The test results are shown in Table 2.
[0055] Table 2 Effect of different proportions of strontium chloride hexahydrate added on high temperature fluidity of the repair material
[0056]
[0057] As can be seen from Table 2, as the amount of strontium chloride hexahydrate added increases, the number of holes caused by the evaporation of strontium chloride components at high temperatures continues to increase, and the apparent porosity in the repair material matrix continues to rise, especially when the amount added is greater than 6wt%, this change trend is more obvious. Therefore, from the perspective of ensuring the density of the repair material layer after firing, this application believes that the amount of strontium chloride hexahydrate added should be ≤6wt%. However, too little strontium chloride hexahydrate will affect its effect on the promotion of the crystal water of magnesium chloride hexahydrate, thereby inhibiting the formation of water clusters in the repair material matrix and reducing the flow performance. This is confirmed by the size of the sample cake area formed after being flattened and placed in a 1200℃ resistance furnace and kept warm for 10 minutes in Table 2. Therefore, it is not difficult to see from this table that in order to obtain good fluidity, the amount of strontium chloride hexahydrate added must not be less than 4wt%. In summary, considering the fluidity and matrix density of the zero-carbon and sulfur-free magnesium repair material, the present application believes that the optimal addition amount of strontium chloride hexahydrate is 4wt% to 6wt%, and the optimal addition ratio of magnesium chloride hexahydrate is 12wt% to 18wt%.
[0058] The hydromagnesite is a natural hydrated basic magnesium carbonate ore, commonly known as natural magnesium white, and its main chemical composition is 3MgCO3·Mg(OH)2·3H2O, and its theoretical crystallization water content is about 14.8%. In the absence of other components, its crystallization water release temperature is 150°C to 350°C. However, due to the promotion and catalytic effect of strontium chloride hexahydrate in this application, the crystallization water release temperature of the hydromagnesite can be significantly reduced by about 50 to 60°C. Therefore, its addition is very beneficial to promoting the formation of the above-mentioned water aggregation zone and improving the fluidity of the repair material at a lower temperature. In addition, hydromagnesite is a complex phase ore of natural magnesite and magnesite, and CO3 in its crystal structure 2- There are two unique phase relationships and uniformly distributed structural water. Compared with natural magnesite, it not only has a lower decomposition reaction temperature (starting at about 350°C and ending at 650°C), but also can obtain mesoporous reticular magnesium oxide particles with large specific surface area and high reaction activity. During the sintering process of the repair material, this magnesium oxide particle will quickly react with the SiO2 micropowder particles in the repair material system to form a high-temperature phase of forsterite, and this reaction manifests as a volume expansion effect, which can effectively block the pores in the repair material layer, thereby improving the sintering strength and slag erosion resistance of the repair material layer. Furthermore, the CaO content in hydromagnesite is relatively high, which has a significant effect on increasing the C / S ratio of the repair material layer, improving the refractoriness of the material system, and purifying molten steel. In order to maximize the above beneficial effects, this application requires that the MgO content in hydromagnesite is ≥40wt% and the particle size is ≤200 mesh. In addition, this application clearly states that the optimal addition amount of hydromagnesite is 4wt% to 6wt%, otherwise, as shown in Table 3, the high-temperature strength of the zero-carbon and sulfur-free magnesium repair material will be seriously reduced. This is because: when the added amount is less than 4wt%, the amount of active magnesium oxide particles generated in the repair material system is small, and the volume expansion effect brought about by the in-situ forsterite reaction cannot completely fill the evaporative pores caused by the discharge of crystal water, making the strength of the repair material layer worse; and when the added amount is greater than 6wt%, there is too much hydromagnesite participating in the decomposition and calcination reaction and the reaction is extremely intense. Although the evaporative pores caused by the discharge of crystal water have been completely filled, a large number of CO2 escape pores generated by its own decomposition still exist in the repair material system. In addition, the intense reaction process will produce serious stress damage, resulting in a large number of destructive cracks distributed in the repair material matrix. The combined effect of the two greatly reduces the high-temperature strength index of the repair material layer.
[0059] Table 3 High temperature flexural strength of zero carbon and sulfur free magnesium repair material with different proportions of hydromagnesite powder added
[0060]
[0061] The silicon dioxide powder is a high-purity micron-sized SiO2, which is required to have a SiO2 content of ≥99.5wt% and an average particle size of ≤10μm. Its main functions in this application are as follows: (1) It can quickly fuse with the crystal water released in the system to form a silica sol with a certain viscosity, which will effectively inhibit the rapid evaporation of the crystal water, so that the material system can efficiently form a water aggregation zone at the repair operation temperature, thereby ensuring the good flow properties of the zero-carbon and sulfur-free magnesium repair material; (2) As a binder for the zero-carbon and sulfur-free magnesium repair material, its binding effect is mainly reflected in the two Aspects: On the one hand, at a relatively low temperature, the silica sol formed by the silica powder has a typical adhesion-promoting effect on the particles and the matrix in the material system; on the other hand, at a high temperature, the micron-sized SiO2 particles will react with the active magnesium oxide particles in the system to form forsterite. The volume expansion effect produced by the reaction effectively fills various pores in the repair material layer. At the same time, the formation of forsterite reduces the amount of liquid phase in the sintered body, improves the degree of direct bonding under the microstructure, and strengthens the connection between the MgO particles and the matrix, that is, finally forms a stable ceramic bonding state. Therefore, according to the aforementioned addition ratio of magnesium chloride hexahydrate, strontium chloride hexahydrate, and hydromagnesite and the amount of effective crystallization water that may be formed at the repair operation temperature, and comprehensively weighing the amount of active magnesium oxide generated and the amount of forsterite reaction in the entire system, the inventor has concluded through a large number of experiments that the optimal addition ratio of the silica powder described in this application is 3wt% to 5wt%.
[0062] The high-efficiency water reducer is one of the macromolecular long-chain organic compounds such as polyethylene glycol, sodium tripolyphosphate, lignin sulfonate, polycarboxylate, etc., which is also commonly referred to as a high-efficiency surfactant. When added to the castable, it can have a good dispersing effect on the fine particles in its matrix, minimize the agglomeration effect, and thus reduce the amount of water used for mixing. In the present application, polyethylene glycol is preferably used as a water reducer to obtain the best dispersing effect on fine particles such as SiO2 silicon micropowder in the zero-carbon and sulfur-free magnesium repair material system. At the initial stage of crystallization water release, a silica sol mucosa with moderate viscosity and uniform distribution can be immediately formed, thereby promoting the system to quickly form a water aggregation zone and quickly achieve a slurry self-flow response. In order to maximize the above effects, further, a polyethylene glycol particle size of ≤200 mesh is selected, and the optimal addition amount is 0.3wt% to 0.5wt%.
[0063] Al+H2O=Al2O3+H2↑ (Reaction 1)
[0064] H2+O2=H2O (Reaction 2)
[0065] The metal aluminum powder is a powdered substance of a single substance Al, and is introduced in this application as a temperature-compensating enhancer. In the zero-carbon and sulfur-free magnesium repair material system, the metal aluminum powder will undergo a violent hydrothermal reaction with the high-temperature water vapor discharged by the crystal water carrier (see reaction 1), generating Al2O3 and H2, and releasing a large amount of heat. Subsequently, the hydrogen reacts spontaneously with the oxygen in the air (see reaction 2), which is also accompanied by a fierce exothermic effect. It can be seen that through these two reactions, the problem of endothermic temperature drop caused by the release and discharge of crystal water, calcination and decomposition of hydromagnesite in the repair material system can be effectively solved, thereby maintaining a sufficient sintering temperature to ensure the sintering performance of the repair material layer. In addition, the Al2O3 generated by reaction 1 will further react in situ with the MgO in the repair material system to generate a high-temperature phase of magnesium-aluminum spinel (melting point of about 2135°C), which improves the direct bonding degree of the microstructure. At the same time, the in-situ reaction is also accompanied by a volume expansion of about 8%. Like the in-situ forsterite reaction, it can also effectively fill various pores in the repair material system, thereby playing an important role in improving the high-temperature strength of the repair material layer, improving heat resistance, and strengthening slag erosion resistance. The inventor measured the endothermic temperature drop value brought by different addition amounts of crystal water carrier (hydromagnesite), and designed multiple groups of experiments to summarize the compensation effect of the amount of metal aluminum powder added on the temperature drop, and therefore believed that the amount of metal aluminum powder added used in this application should be not less than 2wt%, purity ≥98wt%, and particle size ≤200 mesh. However, it was also found in the experiment that when the amount of aluminum powder added is greater than 5wt%, the above-mentioned in-situ spinel reaction is excessive, and the accompanying excessive volume expansion will cause a large amount of stress concentration on the matrix of the repair material layer and cause structural damage. In addition, if the amount of aluminum powder added is too large, the concentration of H2 generated by reaction 1 is too high, and there is a risk of deflagration or even explosion, which is not conducive to on-site safety. Therefore, this application believes that it is appropriate to add 2wt% to 5wt% of aluminum powder.
[0066] The ingredients are prepared according to the raw material formula composition mentioned above and mixed thoroughly to obtain zero-carbon and sulfur-free magnesium repair materials. After packaging, shipment and transportation to the converter to be repaired, the amount of repair material is determined according to the size of the area to be repaired, the depth of the pit and the arrangement in front of the furnace. Then, the amount of repair material is put into the furnace with the help of the scrap steel trough. Through the reciprocating shaking of the furnace, the repair material is quickly gathered to the area to be repaired. After a period of rest and the repair material is sintered, the shaking furnace is reset and production is resumed.
[0067] In addition, the present application also provides a specific sintering performance control method for a zero-carbon and sulfur-free magnesium repair material, that is, on the basis of ensuring the normal preparation ratio principle of the crystal water carrier of the present application, by continuously adjusting the addition ratio (A / H) between the metal aluminum powder and the hydromagnesite, the temperature in the sintering system of the repair material layer and the in-situ spinel reaction rate and the amount of generation can be effectively controlled, thereby achieving the purpose of adjusting the sintering performance. The specific steps are as follows:
[0068] Step 1: Understand the basic data of the converter to be repaired. Focus on the residual temperature T of the furnace during the converter repair. 余 , the amount of single repair material Y and the specific sintering time t given in front of the furnace 给 ;
[0069] Step 2: Use Y and t obtained in step 1 给 The sintering time coefficient ζ of a ton of material is calculated according to the following formula.
[0070] ζ= t 给 / Y (Formula 6)
[0071] Step 3: Use the ζ calculated in step 2 and T obtained in step 1 余 Refer to the table below to select the ratio of aluminum powder to hydromagnesite, i.e. the optimal value of A / H.
[0072] Table 4 Selection table of the best recommended values of A / H determined by furnace temperature and sintering time coefficient
[0073]
[0074] Step 4: According to the optimal value of A / H selected in step 3, the minimum addition ratio (Al) wt% of metal Al powder is calculated as follows:
[0075] (Al) wt% = (A / H) × (hydromagnesite) wt% (Formula 7)
[0076] Step 5: Increase the (Al) wt% value calculated in step 4 by 10% as the final addition ratio of metal aluminum powder, and introduce it in the form of external addition, so that the repair material can be heated to the residual temperature T 余 Conditions, sintering time is adjusted to t 给 The purpose within this range can well meet the production rhythm of steelmaking in front of the furnace.
[0077] The following will combine different application scenarios and design different zero-carbon and sulfur-free magnesium repair material technical solutions based on crystal water flow promotion through specific examples to elaborate on the present invention in detail. However, it is worth noting that these examples are only the best implementation plans for a specific application scenario and do not limit the scope of the present invention.
[0078] Example 1: Zero-carbon and sulfur-free magnesium repair material based on crystal water flow promotion and its sintering performance control method
[0079] This embodiment is for the routine maintenance of a 260-ton converter in a large domestic steel plant. The main products of this converter are SAPH400 series hot-rolled thin plates and 40CrH series alloy bars. The final carbon drawing ([C]≤0.10%) is usually carried out at a carbon content far lower than the product standard, and high-intensity and high-flow bottom blowing gas stirring is used throughout the furnace campaign. The final temperature is high (steel tapping temperature ≥1700℃ accounts for about 50%, ≥1720℃ accounts for about 10%), the slag steel has strong oxidation, the molten pool has large kinetic energy for rolling and eddy current scouring of the furnace lining, and it is difficult to create a slag layer in the furnace lining, which seriously restricts the improvement of the service life of the furnace lining and its repair materials. The average single repair material consumption in front of the furnace is 2.4t, and the average residual temperature of the furnace during each repair is 1350℃. The steel mill requires the sintering time of a single repair to be controlled within 22min.
[0080] (I) Preparation of zero-carbon and sulfur-free magnesium repair material based on crystal water flow promotion
[0081] According to the above smelting conditions, this embodiment will adopt the following weight ratio scheme to prepare a zero-carbon and sulfur-free magnesium repair material based on crystal water flow promotion:
[0082]
[0083] The above components add up to 100% and are mixed to form a basic repair material.
[0084] In addition, in order to further improve the high-temperature fluidity of the repair material and obtain excellent sintering performance, the following additives need to be added to the above basic repair material formula:
[0085]
[0086] Furthermore, in order to cope with the harsh smelting conditions of the converter, in this embodiment, the main raw material information is selected as follows: the magnesia adopts 97-grade fused magnesia, and its MgO content is 96.8wt%; the main component of the magnesium chloride hexahydrate is MgCl2·6H2O, and the purity of this embodiment is as high as 99.2wt%; in order to maximize the effect of promoting the discharge of crystal water, the purity of strontium chloride hexahydrate is selected as 99.2wt% in this embodiment; the hydromagnesite is derived from the Bange Lake ore belt in Tibet, and its MgO content is 40.8wt%; the SiO2 content in the silica micropowder is as high as 99.6wt%, the particle size is not more than 10μm, and D50 is about 5μm; the high-efficiency water reducer in this embodiment uses industrial pure polyethylene glycol; the purity of metallic aluminum powder is 98.2wt%.
[0087] By preparing the ingredients according to the above-mentioned specific raw material requirements and formula composition and mixing them thoroughly, you can get zero-carbon and sulfur-free magnesium repair materials. After packaging, shipping and transportation to the converter to be repaired, the amount of repair materials is determined to be 2.4 tons according to the size of the area to be repaired, the depth of the pit and the plan in front of the furnace. Finally, the amount of repair materials is put into the furnace with the help of scrap steel trough. Through the reciprocating shaking of the furnace, the repair materials are quickly gathered to the area to be repaired. After a period of rest and the repair materials are sintered, the furnace is reset and production is resumed.
[0088] (II) Sintering performance control method
[0089] Based on the above formula, this embodiment can effectively control the temperature in the sintering system of the repair material layer and the reaction speed and amount of in-situ spinel by continuously adjusting the addition ratio of metal aluminum powder to hydromagnesite (A / H), thereby achieving the purpose of adjusting the sintering performance. The specific steps are as follows:
[0090] Step 1: Understand the basic data of the converter to be repaired. From the data obtained in this embodiment, the average residual temperature of the furnace of the converter each time it is repaired is T 余 =1350℃, single repair material consumption Y=2.4 tons, specific sintering time t given in front of the furnace 给 =22min;
[0091] Step 2: Use Y and t obtained in step 1 给 The sintering time coefficient ζ per ton of material is calculated according to (Formula 6).
[0092] ζ=t 给 / Y=22min / 2.4=9.17min
[0093] Step 3: Use ζ = 9.17mim calculated in step 2 and T obtained in step 1 余 =1350℃, according to the data in Table 4, it can be determined that the ratio of the amount of metal aluminum powder to hydromagnesite added, i.e. A / H, should be ≥0.45.
[0094] Step 4: According to the A / H≥0.45 selected in step 3, and from the formula composition of this embodiment, w(hydromagnesite)%=4wt%, the minimum addition ratio (Al)wt% of the metal Al powder can be calculated according to (Formula 7):
[0095] (Al) wt% = 0.45 × (hydromagnesite) wt% = 0.45 × 4 wt% = 1.8 wt%
[0096] Step 5: Increase the (Al) wt% value calculated in step 4 by 10% to obtain 1.98wt%. According to the requirement in the previous text that at least 2 wt% of metal Al powder should be added to achieve the best effect, this embodiment uses 2wt% as the final addition ratio of metal aluminum powder and introduces it in an external form. This can achieve the purpose of well controlling the sintering time of the repair material to within 22 minutes under the condition of an average residual temperature of the furnace at 1350°C, which meets the requirements of fast-paced steelmaking in front of the furnace.
[0097] Example 2: Zero-carbon and sulfur-free magnesium repair material based on crystal water flow promotion and its sintering performance control method
[0098] This example is for the routine maintenance of a 150-ton converter of a domestic steel company. The converter mainly produces SAE1006, Q195, 3SP series high-quality carbon structural steel and other steel types, which belong to the category of low-carbon steel. The product forms are mostly ribbed steel bars and high-speed wire rods that are more common in the market. Its main smelting characteristics are: high bottom blowing intensity, high-temperature molten steel has a strong scouring effect on the furnace lining and repair material layer; the molten steel end point [O] is high, the final slag is highly oxidizing, the splashing slag protection effect is poor, and the penetration and erosion ability of the furnace lining bricks and their repair material layers is strong; the steel tapping temperature is high, mainly concentrated in 1650~
[0099] According to follow-up investigation, the average amount of material used for a single repair in front of the furnace is 2 tons, and the average residual temperature of the furnace during each repair is about 1200℃. The company hopes that the sintering time for a single repair can be controlled within 15 minutes.
[0100] (I) Preparation of zero-carbon and sulfur-free magnesium repair material based on crystal water flow promotion
[0101] According to the above smelting conditions, this embodiment will adopt the following weight ratio scheme to prepare a zero-carbon and sulfur-free magnesium repair material based on crystal water flow promotion:
[0102]
[0103]
[0104] The above components add up to 100% and are mixed to form a basic repair material.
[0105] In addition, in order to further improve the high-temperature fluidity of the repair material and obtain excellent sintering performance, the following additives need to be added to the above basic repair material formula:
[0106]
[0107] Furthermore, in order to cope with the harsh smelting conditions of the converter, in this embodiment, the specific raw material information selected is as follows: the magnesia is 97-grade sintered magnesia, and its MgO content is 97.1wt%; the main component of the magnesium chloride hexahydrate is MgCl2·6H2O, and the purity of this embodiment is as high as 98.8wt%; in order to maximize the effect of promoting the discharge of crystal water, the purity of strontium chloride hexahydrate is selected as 99.4wt% in this embodiment; the hydromagnesite comes from the Bange Lake ore belt in Tibet, and its MgO content is 41.5wt%; the SiO2 content in the silica micropowder is as high as 99.7wt%, its particle size is not more than 10μm, and D50 is about 4μm; the high-efficiency water reducer in this embodiment uses industrial pure polyethylene glycol; the purity of metallic aluminum powder is 98.5wt%.
[0108] By preparing the ingredients according to the above-mentioned specific raw material requirements and formula composition and mixing them thoroughly, you can get zero-carbon and sulfur-free magnesium repair materials. After packaging, shipping and transportation to the converter to be repaired, the amount of repair materials is determined to be 2 tons according to the size of the area to be repaired, the depth of the pit and the plan in front of the furnace. Finally, with the help of the scrap steel trough, the repair materials are put into the furnace. Through the reciprocating shaking of the furnace, the repair materials are quickly gathered to the area to be repaired. After a period of rest and the repair materials are sintered, the furnace is reset and production is resumed.
[0109] (II) Sintering performance control method
[0110] Based on the above formula, this embodiment can effectively control the temperature in the sintering system of the repair material layer and the reaction speed and amount of in-situ spinel by continuously adjusting the addition ratio of metal aluminum powder to hydromagnesite (A / H), thereby achieving the purpose of adjusting the sintering performance. The specific steps are as follows:
[0111] Step 1: Understand the basic data of the converter to be repaired. From the data obtained in this embodiment, the average residual temperature of the furnace of the converter each time it is repaired is T 余 =1200℃, single repair material amount Y=2 tons, specific sintering time t given in front of the furnace 给 =15min;
[0112] Step 2: Use Y and t obtained in step 1 给 The sintering time coefficient ζ per ton of material is calculated according to (Formula 6).
[0113] ζ=t 给 / Y=15min / 2=7.5min
[0114] Step 3: Use ζ=7.5mim calculated in step 2 and T obtained in step 1 余 =1200℃, according to the data in Table 4, it can be determined that the ratio of the amount of metal aluminum powder to the amount of hydromagnesite added, i.e. A / H, should be ≥0.65.
[0115] Step 4: According to the A / H≥0.65 selected in step 3, and from the formula composition of this embodiment, w(hydromagnesite)%=5wt%, the minimum addition ratio (Al)wt% of the metal Al powder can be calculated according to (Formula 7):
[0116] (Al) wt% = 0.65 × (hydromagnesite) wt% = 0.65 × 5 wt% = 3.25 wt%
[0117] Step 5: The (Al) wt% value calculated in step 4 is increased by 10% to obtain 3.6wt%. In this embodiment, 3.6wt% is used as the final addition ratio of metal aluminum powder, and it is introduced in an external form, so that the sintering time of the repair material can be well controlled to within 15min under the condition of an average residual temperature of the furnace of 1200°C, which better meets the requirements of fast-paced steelmaking in front of the furnace.
[0118] Example 3: Zero-carbon and sulfur-free magnesium repair material based on crystal water flow promotion and its sintering performance control method
[0119] This embodiment is carried out for the actual daily maintenance of a 120-ton converter in a domestic steel plant. The converter mainly produces medium and high carbon steels such as Q235B, Q255B, 45#, HRB300, and mainly produces and sells high-speed wire rods and construction steel bars. The smelting characteristics of this converter are: the tapping temperature is relatively low, usually 1620℃~1640℃; the final slag basicity is high, 3.5~4.2; the final slag FeO (wt) is less than 10%, the slag viscosity is moderate, and the splashing slag protection effect is good; the main reason for the damage of the repair material layer is poor sintering performance and insufficient strength. According to the feedback from the front of the furnace, the average single repair material consumption of the converter is 1.6t. Due to the large temperature drop of steel tapping, the average residual temperature of the furnace during each repair is only about 1000℃. In order to maximize the production efficiency of the workshop, the company's planning and scheduling department requires that the single repair sintering time should not exceed 10min, and accidents such as material overturning and material collapse are not allowed.
[0120] (I) Preparation of zero-carbon and sulfur-free magnesium repair material based on crystal water flow promotion
[0121] According to the above smelting conditions, this embodiment will adopt the following weight ratio scheme to prepare a zero-carbon and sulfur-free magnesium repair material based on crystal water flow promotion:
[0122]
[0123] The above components add up to 100% and are mixed to form a basic repair material.
[0124] In addition, in order to further improve the high-temperature fluidity of the repair material and obtain excellent sintering performance, the following additives need to be added to the above basic repair material formula:
[0125]
[0126] Furthermore, in order to cope with the harsh smelting conditions of the converter, in this embodiment, the specific raw material information selected is as follows: the magnesia is 92 grade dead-burned magnesia, and its MgO content is 92.5wt%; the main component of the magnesium chloride hexahydrate is MgCl2·6H2O, and the purity of this embodiment is as high as 98.5wt%; in order to maximize the effect of promoting the discharge of crystal water, the purity of strontium chloride hexahydrate is selected as 99.6wt% in this embodiment; the hydromagnesite is derived from the salt lake area of the Qinghai-Tibet Plateau, and its MgO content is 41.8wt%; the SiO2 content in the silica powder is as high as 99.8wt%, the particle size is not more than 10μm, and D50 is about 3μm; the high-efficiency water reducer described in this embodiment still uses industrial pure polyethylene glycol; the purity of metallic aluminum powder is 98.8wt%.
[0127] By preparing the ingredients according to the above-mentioned specific raw material requirements and formula composition and mixing them thoroughly, you can get zero-carbon and sulfur-free magnesium repair materials. After packaging, shipping and transportation to the converter to be repaired, the amount of repair materials is determined to be 1.6 tons according to the size of the area to be repaired, the depth of the pit and the plan in front of the furnace. Finally, with the help of the scrap steel trough, the repair materials are put into the furnace. Through the reciprocating shaking of the furnace, the repair materials are quickly gathered to the area to be repaired. After a period of rest and the repair materials are sintered, the furnace is reset and production is resumed.
[0128] (II) Sintering performance control method
[0129] Based on the above formula, this embodiment can effectively control the temperature in the sintering system of the repair material layer and the reaction speed and amount of in-situ spinel by continuously adjusting the addition ratio of metal aluminum powder to hydromagnesite (A / H), thereby achieving the purpose of adjusting the sintering performance. The specific steps are as follows:
[0130] Step 1: Understand the basic data of the converter to be repaired. From the data obtained in this embodiment, the average residual temperature of the furnace of the converter each time it is repaired is T 余 =1000℃, single repair material amount Y=1.6 tons, specific sintering time t given in front of the furnace 给 =10min;
[0131] Step 2: Use Y and t obtained in step 1 给 The sintering time coefficient ζ per ton of material is calculated according to (Formula 6).
[0132] ζ=t 给 / Y=10min / 1.6=6.25min
[0133] Step 3: Use ζ=6.25mim calculated in step 2 and T obtained in step 1 余=1000℃, according to the data in Table 4, it can be determined that the ratio of the amount of metal aluminum powder to the amount of hydromagnesite added, i.e. A / H, should be ≥0.85.
[0134] Step 4: According to the A / H≥0.85 selected in step 3, and from the formula composition of this embodiment, w(hydromagnesite)%=6wt%, the minimum addition ratio (Al)wt% of the metal Al powder can be calculated according to (Formula 7):
[0135] (Al) wt% = 0.85 × (hydromagnesite) wt% = 0.85 × 6 wt% = 5.1 wt%
[0136] Step 5: Increase the (Al) wt% value calculated in step 4 by 10% to obtain 5.6wt%. According to the requirement that the optimal addition ratio of metal Al powder should not be more than 5wt%, the present embodiment uses 5wt% as the final addition ratio of metal aluminum powder and introduces it in an external form. Under the condition that the average residual temperature of the furnace is only 1000°C, the sintering time of the repair material can be controlled within 10min to the greatest extent, thus better meeting the steel plant's requirements for efficient steelmaking.
[0137] The actual use effects achieved by the above-mentioned Examples 1 to 3 are summarized in Table 2, and compared with the traditional asphalt-bonded magnesium-carbon repair materials used in various converters.
[0138] Table 5 Actual application effects achieved by various embodiments
[0139]
[0140] As can be seen from Table 5, the technical solution of the present application has the ability to quickly form a water aggregation zone, the crystallized water has an effective flow-promoting effect at high temperatures, and has good high-temperature flow performance. Compared with traditional magnesium-carbon repair materials, the sintering time required for the present application is greatly shortened (down 45% to 67%), and the service life is greatly improved (increased 40% to 70%). All embodiments can better meet the basic requirements of efficient and fast-paced steelmaking in various steel mills, and have achieved good application effects.
Claims
1. A zero-carbon and sulfur-free magnesium repair material based on crystal water flow promotion, characterized in that: Made from the following raw materials in parts by weight: The above components add up to 100% and are mixed to form a basic repair material.
2. The zero-carbon and sulfur-free magnesium repair material based on crystal water flow promotion according to claim 1 is characterized in that: The magnesia is one or more of sintered magnesia or fused magnesia, and the MgO content of the magnesia raw material is ≥80wt%.
3. The zero-carbon and sulfur-free magnesium repair material based on crystal water flow promotion according to claim 1 is characterized in that: The purity of the strontium chloride hexahydrate is ≥99wt%.
4. The zero-carbon and sulfur-free magnesium repair material based on crystal water flow promotion according to claim 1 is characterized in that: The repair material also needs to be added with a high-efficiency water reducing agent, and the added proportion is 0.3wt% to 0.5wt% of the basic repair material.
5. The zero-carbon and sulfur-free magnesium repair material based on crystal water flow promotion according to claim 4 is characterized in that: The high-efficiency water reducing agent is one of polyethylene glycol, sodium tripolyphosphate, lignin sulfonate or polycarboxylate.
6. The zero-carbon and sulfur-free magnesium repair material based on crystal water flow promotion according to claim 5, characterized in that: The preferred high-efficiency water reducing agent is polyethylene glycol, with a particle size of ≤200 mesh.
7. The zero-carbon and sulfur-free magnesium repair material based on crystal water flow promotion according to claim 1 is characterized in that: The repair material also needs to be added with metal aluminum powder, the addition ratio of which is 2wt% to 5wt% of the basic repair material, and the particle size of the aluminum powder is ≤200 mesh.
8. The specific sintering performance control method of the magnesium repair material according to claim 7 is characterized in that The following steps are included: Step 1: Understand the basic data of the converter to be repaired: focus on the residual temperature T of the furnace during the converter repair 余 , the amount of single repair material Y and the specific sintering time t given in front of the furnace 给 ; Step 2: Use Y and t obtained in step 1 给 Calculate the sintering time coefficient ζ of a ton of material according to the following formula; ζ = t 给 / Y (Equation 6) Step 3: Use the ζ calculated in step 2 and T obtained in step 1 余 , refer to the table below to select the ratio of aluminum powder to hydromagnesite, i.e. the optimal value of A / H; Table 4 Selection table of the best recommended values of A / H determined by furnace temperature and sintering time coefficient Step 4: According to the optimal value of A / H selected in step 3, the minimum addition ratio (Al) wt% of metal Al powder is calculated as follows: (Al) wt% = (A / H) × (hydromagnesite) wt% (Formula 7) Step 5: Increase the (Al) wt% value calculated in step 4 by 10% as the final addition ratio of metal aluminum powder, and introduce it in the form of external addition, so that the repair material can be heated to the residual temperature T 余 Conditions, sintering time is adjusted to t 给 The purpose within this range can well meet the production rhythm of steelmaking in front of the furnace.
Citation Information
Patent Citations
Carbon-free converter mending material
CN106747505A
Water-based large fabric for converter and preparation method of water-based large fabric
CN116751067A
Environment-friendly water-based magnesium converter repairing material capable of being rapidly sintered and preparation method thereof
CN115385668A
Batch composition for producing refractory ceramic shaped body, shaped body produced therefrom and use thereof
CN1407955A
Spraying material for repairing lining of steelmaking electric furnace and method for repairing lining of steelmaking electric furnace using the same
JP2007039255A